Use of 3‐D digital subtraction rotational angiography during cardiac catheterization of infants and adults with congenital heart diseases. Issue 4 (14th July 2017) - Surendran, Sushitha; Waller, B. Rush; Elijovich, Lucas; Agrawal, Vijaykumar; Kuhls‐Gilcrist, Andrew; Johnson, Jason; Fagan, Thomas; Sathanandam, Shyam K.
Abstract: Objective: To compare image quality, radiation and contrast doses required to obtain 3D‐Digital subtraction rotational angiography (3D‐DSRA) with 3D‐Digital rotational angiography (3D‐DRA) in infants (children ≤ 2 years of age) and adults with congenital heart diseases (ACHD). Background: 3D‐DRA can be performed with radiation doses comparable to bi‐plane cine‐angiography. However, 3D‐DRA in infants requires a large contrast volume. The resolution of 3D‐DRA performed in ACHD patients is limited by their soft tissue density. We hypothesized that the use of 3D‐DSRA could help alleviate these concerns. Methods: Radiation (DAP) and contrast doses required to obtain 3D‐DSRA was compared with 3D‐DRA in 15 age‐, size‐, and intervention‐matched infants and 15 ACHD patients. The diagnostic quality and utility of these two modalities were scored by 4 qualified independent observers. Results: Both in infants and adults, the median contrast volume for 3D‐DSRA was lower than 3D‐DRA (0.98 vs. 1.81 mL/kg; P  < 0.001 and 0.92 vs. 1.4 mL/kg; P  < 0.001, respectively) with an increased DAP (median: 188 vs. 128 cGy cm 2 ; P  = 0.068 and 659 vs. 427 cGy cm 2 ; P  = 0.045, respectively). The diagnostic quality and utility scores for rotational‐angiography, and 3D‐reconstruction were superior for 3D‐DSRA (score = 94 vs. 80%, P  = 0.03 and 90 vs.79%, P  = 0.01, respectively) and equivalent for multi‐planar‐reformation and 3D‐roadmapping in ACHD patients compared with 3D‐DRA. All scores for both modalities were equivalent for infants. Conclusions: 3D‐DSRA can be acquired using lower contrast volume with a mildly higher radiation dose than 3D‐DRA in infants and ACHD patients. The diagnostic quality and utility scores for 3D‐DSRA were higher in ACHD patients and equivalent for infants compared with 3D‐DRA.